Design and Implementation of an Off-The-Shelf Controller for Power Electronics Research and Teaching - Diaz-Diaz, M; Uriarte-Gonzalez, M; Aravena-Carrasco, J (Institute of Electrical and Electronics Engineers Inc., 2022)
Several off-the-shelf real-time control systems are available for industrial and academic applications. These systems enable real-time control and prototyping of power electronic applications. However, most of these systems have a considerable cost and are inflexible, limiting their teaching and academic research usage. Consequently, this paper presents the design and implementation of a control platform based on a low-cost easy-to-program microcontroller from Texas Instruments. The proposed control platform is intended for rapid-control-prototyping, and it considers optic PWM outputs, isolated sensing of voltage/currents, multipurpose input-outputs, and hardware protections. Experimental results are presented to validate the usefulness of the proposed control platform. © 2022 IEEE.